Synthesis and characterization of CoFe2O4 thin films for solar absorber application. (1st June 2020) - Labchir, N.; Hannour, A.; Hssi, A. Ait; Vincent, D.; Abouabassi, K.; Ihlal, A.; Sajieddine, M.
Abstract: Spinel oxides synthetized by the electrochemical route can be used in different technological areas. In the present work, cobalt ferrite (CoFe2 O4 ) thin films were deposited from sulfate bath on FTO-coated glass substrate by linear sweep voltammetry technique (LSV). We have investigated the effect of applied magnetic field B (AMF B) up to 0.5 T on the electrochemical response, the crystallographic texture, the morphology, the semiconductor type and the optical properties of the elaborated films. The structural and compositional analysis confirmed the synthesis of a well-crystallized CoFe2 O4 with a good stoichiometry after an annealing treatment at 500 °C. Moreover, the CoFe2 O4 films exhibited a p-type semiconductor as confirmed by the photo-electrochemical and Mott-Schottky tests. In addition, an increasing in the absorbance in the visible-UV region is observed under AMF B. Consequently, the magneto-electrodeposited CoFe2 O4 thin films have a direct band gap energy of 1.5 eV.